Improved pain control with adductor canal block using liposomal bupivacaine after total knee replacement: a retrospective cohort study - Akshay Lakra, MD; Matthew Grosso, MD; Emma L. Jennings, BS; H. John Cooper, MD; Roshan P. Shah, MD; Jeffrey A. Geller, MD (Arthroplasty Today, 2019)
Background: Adductor canal blocks (ACBs), typically administered with a local anesthetic such as bupivacaine, help control perioperative pain after total knee arthroplasty. Recently, liposomal bupivacaine (LB) was introduced in an attempt to extend the duration of analgesia, used primarily in periarticular injections (PAIs). The purpose of this study was to compare pain control and early perioperative outcomes with ACB using LB vs standard bupivacaine (SB). Methods: We retrospectively compared pain control in a group of 75 patients with ACB and PAI with SB to that of a cohort of 75 patients who received ACB and PAI with LB. The primary outcome measure was pain measured using the visual analog score. The secondary outcome measures were morphine equivalents of pain medication (ME), physical therapy distance ambulated, disposition status, and length of stay. Results: There were no significant differences between the two cohorts for age, gender, body mass index, preoperative diagnosis, or American Society of Anesthesiologists. Visual analog scores were significantly lower in the LB group for postoperative day (POD) 0 (2.1 vs 2.8, P = .046), POD 1 (2.2 vs 3.3, P < .001), and POD 2 (2.1 vs 3.7, P = .001) than those in the SB group. The LB group consumed significantly fewer ME on the POD 0 (18.7 vs 25.2, P = .02) and POD 1 (23.4 vs 37.8, P = .003), as well as overall ME/day (24.6 vs 41.7, P < .001). The LB group walked more on POD 0 (261.6 vs 108.2, P < .001) and POD 1 (761.5 vs 372.0, P < .001). Conclusions: We report improved outcomes across all measures for the LB group. There were no adverse events. This study supports the use of LB for ACBs in total knee arthroplasty. Keywords: Total knee arthroplasty, Adductor canal block, Pain, Liposomal bupivacaine, Bupivacaine